2016
DOI: 10.1016/j.drugalcdep.2016.09.021
|View full text |Cite
|
Sign up to set email alerts
|

The relationships of childhood trauma and adulthood prescription pain reliever misuse and injection drug use

Abstract: Background We examined associations between childhood trauma and adulthood prescription pain reliever misuse (PPRM) and injection drug use (IDU) in a nationally-representative U.S. sample to further understanding of factors associated with these epidemics. Methods National Longitudinal Study of Adolescent to Adult Health data (N=12,288) yielded nine childhood traumas: neglect; emotional, physical, sexual abuse; parental incarceration and binge drinking; witnessed, threatened with, and experienced violence. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 44 publications
(53 reference statements)
2
54
1
3
Order By: Relevance
“…Limited research has assessed the relationship between school experiences and pain reliever misuse among high school students nationwide. Much of the literature has focused on other potential risk factors such as peer norms, childhood trauma, and socioeconomic influences on pain reliever misuse (Ford, Sacra, & Yohros, 2017;Oluwoye, Merianos, & Nabors, 2017;Quinn et al, 2016;Quinn et al, 2019). Thus, assessing school-related risk factors may be beneficial for guiding future improvements in school-based substance use programs.…”
Section: Introductionmentioning
confidence: 99%
“…Limited research has assessed the relationship between school experiences and pain reliever misuse among high school students nationwide. Much of the literature has focused on other potential risk factors such as peer norms, childhood trauma, and socioeconomic influences on pain reliever misuse (Ford, Sacra, & Yohros, 2017;Oluwoye, Merianos, & Nabors, 2017;Quinn et al, 2016;Quinn et al, 2019). Thus, assessing school-related risk factors may be beneficial for guiding future improvements in school-based substance use programs.…”
Section: Introductionmentioning
confidence: 99%
“…A history of witnessing violence, experiencing a natural disaster, or a lifetime history of Post-Traumatic Stress Disorder (PTSD) were associated with an increased likelihood of NMUPD (Lowe, Sampson, Young, & Galea, 2017; McCauley et al, 2010; Quinn et al, 2016), particularly with the increased non-medical use (NMU) of opiates (Smith, Smith, Cercone, McKee, & Homish, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…ACEs are the main factors in the tendency toward addiction (Quinn et al, 2016). Retrospective self-report data have shown that ACEs are key factors in the etiology of illegal drugs abuse (Anda et al, 2006) and can be responsible for half to two-thirds of problems related to the substance abuse in adulthood (Dube et al, 2003).…”
mentioning
confidence: 99%
“…For example, one study in 2016 showed a clear relationship between the number of childhood traumatic experiences and an increase in the risk of substance abuse in adulthood. People who reported five or more ACEs were exposed to substance abuse, and their likelihood of using injective drugs was three times more than normal people (Quinn et al, 2016). Another study indicates that above 80% of patients that were searching for a treatment of drug abuse, experienced at least one type of childhood traumas and two-thirds of them had witnessed violence in childhood (Tsavoussis, Stawicki, Stoicea, & Papadimos, 2014).…”
mentioning
confidence: 99%